Novel Prediction Using TB-mBJ of Electronic Properties, Magnetic Exchange Couplings, and Half-Metallicity in CrCaSe Materials - Sahraoui, H. R.; Doumi, B.; Mokaddem, A.; Bensaid, D.; Boutaleb, M.; Tadjer, A.; Yakoubi, A.; Sayede, A.
In this study, we have performed investigations on the structural stability, elec-tronic band structures, magnetic exchange couplings, and half-metallic performance of CrxCa1-xSe materials using computational methods of density functional theory via GGA-WC, GGA-PBE and, TB-mBJ exchange-correlation potentials. The CrxCa1–xSe compounds are thermodynamically stable and synthesizable owing to their negative formation energies. The structural parameters of CrxCa1–xSe with GGA-WC and GGA-PBE approximations appear to be in excellent concordance compared to the experi-mental data and recent theoretical calculations. According to GGA-PBE and TB-mBJ calculations, the CrxCa1–xSe compounds revealed integral magnetic moments and a half-metallic behavior with better half-metallic gaps, and spin-polarization of 100%. The CrxCa1–xSe alloys appear to be better materials for use in spintronic devices.
Keywords: Физика